2021
DOI: 10.2196/25578
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Abstinence After Completing a Comprehensive Digital Smoking Cessation Program Incorporating a Mobile App, Breath Sensor, and Coaching: Cohort Study

Abstract: Background Despite decreasing prevalence over the last several decades, cigarette smoking remains the leading cause of preventable death and disease, underscoring the need for innovative, effective solutions. Pivot is a novel, inclusive smoking cessation program designed for smokers along the entire spectrum of readiness to quit. Pivot leverages proven methods and technological advancements, including a personal portable breath carbon monoxide sensor, smartphone app, and in-app text-based coaching.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
(77 reference statements)
1
15
0
Order By: Relevance
“…Moreover, longer term quit rates reported in the literature typically refer to the proportion of individuals abstinent at a given point in time, rather than capturing continuous abstinence across multiple follow-ups, a more stringent measurement of favorable treatment outcomes. Thus, the 26-week point prevalence abstinence rate of 35.9% observed among QG participants not only exceeds long term quit rates reported for other digital smoking cessation interventions, such as iCanQuit, an ACT-based smoking cessation application (29.6% quit rate at 6 months post-treatment) 20 , and Craving to Quit, a mobile app based mindfulness training program (11% abstinence rate at 6 months post-baseline) 21 , but our primary outcome of continuous abstinence at 6 and 12 months (27.2% and 22.6%, respectively) far exceeds those reported for various digital programs, including iCanQuit (prolonged abstinence rate of 13.8% at 12 months post-treatment) 20 , Happy Quit, a text messaging based intervention (6.5% at 6 months post-treatment) 22 , and is comparable to Pivot's 23.8% (ITT) continuous abstinence at 7 months post-enrollment 23 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, longer term quit rates reported in the literature typically refer to the proportion of individuals abstinent at a given point in time, rather than capturing continuous abstinence across multiple follow-ups, a more stringent measurement of favorable treatment outcomes. Thus, the 26-week point prevalence abstinence rate of 35.9% observed among QG participants not only exceeds long term quit rates reported for other digital smoking cessation interventions, such as iCanQuit, an ACT-based smoking cessation application (29.6% quit rate at 6 months post-treatment) 20 , and Craving to Quit, a mobile app based mindfulness training program (11% abstinence rate at 6 months post-baseline) 21 , but our primary outcome of continuous abstinence at 6 and 12 months (27.2% and 22.6%, respectively) far exceeds those reported for various digital programs, including iCanQuit (prolonged abstinence rate of 13.8% at 12 months post-treatment) 20 , Happy Quit, a text messaging based intervention (6.5% at 6 months post-treatment) 22 , and is comparable to Pivot's 23.8% (ITT) continuous abstinence at 7 months post-enrollment 23 .…”
Section: Discussionmentioning
confidence: 72%
“…perpetuity. preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted August 24, 2021. ; https://doi.org/10.1101/2021.08.19.21262270 doi: medRxiv preprint including iCanQuit (prolonged abstinence rate of 13.8% at 12 months post-treatment) (20), Happy Quit, a text messaging based intervention (6.5% at 6 months post-treatment) (22), and is comparable to Pivot's 23.8% (ITT) continuous abstinence at 7 months post-enrollment (23).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, younger adults and certain ethnic and racial groups are less likely to seek help or use treatment [20]. Although there is a growing body of evidence evaluating [21,22] and testing the effectiveness of cessation apps [13][14][15]23,24], there is little known about who these apps can reach and benefit when offered, for free, to an entire population. Since most publicly funded tobacco cessation programs are designed to provide access to underserved communities and groups disproportionately impacted by tobacco use, both effectiveness Lack of access to smartphone technology can serve as an obstacle to digital or app-based treatments.…”
Section: Principal Resultsmentioning
confidence: 99%
“…Furthermore, a smoking cessation intervention that leveraged portable carbon monoxide sensors reported promising results, with significant shifts in attitudes toward quitting (eg, readiness to quit and confidence in quitting) [21]. Longer-term (ie, 3 months after the intervention) results revealed increased quit rates and continuous abstinence [22]. This intervention built off several studies that suggested that receiving real-time biometric data from carbon monoxide sensors could be educational and motivational, thus leading to positive changes related to smoking attitudes and behaviors [23][24][25][26].…”
Section: Although Approximately 145 Million Persons In the Unitedmentioning
confidence: 99%